Effect of the glumes on physiological quality of sweet sorghum seeds during maturation process - Tillmann, Maria Angela André; dos Santos, Dora Suely Barbosa; Peters, José Antônio (Pesquisa Agropecuaria Brasileira, 1991)
This research was done with the aim of measuring the glumes effect on the physiological quality of sweet sorghum (Sorghum bicolor (L.) Moench) seeds, harvested at different maturation stages, during three years. Seed lots were separated into three groups: with glumes, without glumes and mixture of both. The parameters evaluated were: seed moisture content, dry weight, germination pre-drying and cold test. During the last two years germination was tested at harvest and after 14 days of storage at room conditions. The results indicate that: a. In immature seeds, the group without glumes showed a higher percentage of germination than the other two groups, with glumes and mixture, suggesting the presence of inhibitory substances in the glumes. b. Storage at room conditions, during 14 days, increased the germination of seeds immaturely harvested. c. The high percentage of seed germination (over 80%) observed during three years showed that sweet sorghum seeds have no dormancy at physiological maturation.